A Plant Gene Encoding One-Heme and Two-Heme Hemoglobins With Extreme Reactivities Toward Diatomic Gases and Nitrite - Villar, Irene; Larrainzar, Estíbaliz; Milazzo, Lisa; Pérez-Rontomé, Carmen; Rubio, Maria C.; Smulevich, Giulietta; Martínez, Jesús I.; Wilson, Michael T.; Reeder, Brandon; Huertas, Raul; Abbruzzetti, Stefania; Udvardi, Michael; et al. (Frontiers in Plant Science, 2020)
In plants, symbiotic hemoglobins act as carriers and buffers of O2 in nodules, whereas phytoglobins (Glbs) are ubiquitous in tissues and may perform multiple, but still poorly defined, functions related to O2 and/or nitric oxide (NO). Here we have identified a Glb gene of the model legume Medicago truncatula with unique properties. The gene, designated MtGlb1-2, generates four alternative spliced forms encoding Glbs with one or two heme domains and 215 to 351 amino acid residues. This is more than double the size of any hemoglobin from plants or other organisms. A combination of molecular, cellular, biochemical and biophysical methods was used to characterize these novel proteins. MtGlb1-2 is transcriptionally activated by hypoxia and the expression is further enhanced by an NO source. The gene is preferentially expressed in the meristems and vascular bundles of roots and nodules. Two of the proteins, bearing one or two hemes, were characterized using mutants in the distal histidines of the hemes. The Glbs are extremely reactive towards the physiological ligands O2, NO and nitrite. They show very high O2 affinities, NO dioxygenase activity (in the presence of O2) and nitrite reductase activity (in the absence of O2) compared with the hemoglobins from vertebrates and other plants. We propose that these Glbs act as either NO scavengers or NO producers depending on the O2 tension in the plant tissue, being involved in the fast and fine tuning of NO concentration in the cytosol in response to sudden changes in O2 availability.